Molecular detection by some virulence genes of Salmonella enterica subsp. enterica isolated from the stool of children with diarrhea (Baghdad Science Journal, 2023)
Diarrhea is a real disease in childhood which could cause death. Therefore, this study was conducted to isolate Salmonella from 350 stool samples taken from children under five years in age, suffering from diarrhea during the period from March 2019 to March 2020 in Tikrit city / Iraq. The results showed the possibility to isolate ten isolates of Salmonella enterica subsp. Enterica, an infection rate, represents 2.875% of the total rate of patients who suffer from diarrhea. The virulence genes were investigated for ten isolates of S. enterica subsp. enterica, the result is that all isolates possessed the genes stn, invA, lpfA with an appearance percentage of 100%, while the percentage of appearance of pefA and fimH genes was 80% and 60%, respectively. All these isolates as Iraqi detection have been submitted to NCBI then accepted as   ten Iraqi strains were in NCBI. All strains were concordance of 99-100% with the Salmonella enterica subsp. enterica Strains of Taiwan (CP085821.1), the United Kingdom (OU943338.1), China (CP085699.1), South Korea (CP077760.1), Pakistan (OK035700.1) and Hong Kong (CP0823381.1) in addition to four US states.